A self‐assembled nanomedicine for glucose supply interruption‐amplified low‐temperature photothermal therapy and anti‐prometastatic inflammatory processes of triple‐negative breast cancer - Mingcheng Wang; Huixi Yi; Zhixiong Zhan; Zitong Feng; Gang‐Gang Yang; Yue Zheng; Dong‐Yang Zhang (Aggregate)
Abstract The poor prognosis of triple‐negative breast cancer (TNBC) results from its high metastasis, whereas inflammation accompanied by excessive reactive oxygen species (ROS) is prone to aggravate tumor metastasis. Although photothermal therapy (PTT) has extremely high therapeutic efficiency, the crafty tumor cells allow an increase in the expression of heat shock proteins (HSPs) to limit its effect, and PTT‐induced inflammation is also thought to be a potential trigger for tumor metastasis. Herein, myricetin, iron ions, and polyvinylpyrrolidone were utilized to develop nanomedicines by self‐assembly strategy for the treatment of metastatic TNBC. The nanomedicines with marvelous water solubility and dispersion can inhibit glucose transporter 1 and interfere with mitochondrial function to block the energy supply of tumor cells, achieving starvation therapy on TNBC cells. Nanomedicines with excellent photothermal conversion properties allow down‐regulating the expression of HSPs to enhance the effect of PTT. Interestingly, the broad spectrum of ROS scavenging ability of nanomedicines successfully attenuates PTT‐induced inflammation as well as influences hypoxia‐inducible factors‐1α/3‐phosphoinositide‐dependent protein kinase 1 related pathway through glycometabolism inhibition to reduce tumor cell metastasis. Moreover, the nanomedicines have negligible side effects and good clinical application prospects, which provides a valuable paradigm for the treatment of metastatic TNBC through glycometabolism interference, anti‐inflammation, starvation, and photothermal synergistic therapy.